2019
DOI: 10.1177/1179547619831026
|View full text |Cite
|
Sign up to set email alerts
|

Acute Symptomatic Sinus Bradycardia in High-Dose Methylprednisolone Therapy in a Woman With Inflammatory Myelitis: A Case Report and Review of the Literature

Abstract: High dose corticosteroid therapy is widely used as attack therapy of inflammatory central nervous system disorders and can induce several adverse reactions. Bradycardia is an infrequent event after corticosteroids administration and is often asymptomatic. We report a case of a woman admitted to the neurological department of our hospital for paraesthesias of the lower limbs. She received adiagnosis of inflammatory myelitis and high dose corticosteroid therapy was prescribed. During the therapy she complained o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…A literature review revealed that steroid-induced bradycardia is likely underdiagnosed because most patients are asymptomatic,2 7 8 in contrast to our case where the patient experienced symptoms. Although the bradycardia resolves spontaneously after discontinuation of the medication, it is also crucial to rule out other, more prevalent causes of bradycardia, such as hypothyroidism, electrolyte imbalance and the use of drugs including beta-blockers, calcium channel blockers and digitalis.…”
Section: Discussioncontrasting
confidence: 68%
“…A literature review revealed that steroid-induced bradycardia is likely underdiagnosed because most patients are asymptomatic,2 7 8 in contrast to our case where the patient experienced symptoms. Although the bradycardia resolves spontaneously after discontinuation of the medication, it is also crucial to rule out other, more prevalent causes of bradycardia, such as hypothyroidism, electrolyte imbalance and the use of drugs including beta-blockers, calcium channel blockers and digitalis.…”
Section: Discussioncontrasting
confidence: 68%
“…Corticosteroids are among the agents that can cause bradycardia. 18 Direct corticosteroids on the myocardium, altered responses to catecholamines, and electrolyte shifts are among the proposed mechanisms underlying corticosteroids associated with bradycardia. 19 In our patients, corticosteroid was not discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose intravenous prednisolone might cause acute sinus bradycardia 289 , 290 or, in MS patients, sinus tachycardia, bradycardia, and rarely AF and VT 289…”
Section: Treatment Of Sars-cov-2 Infectionmentioning
confidence: 99%